Swath sonar bathymetry during R/V Heincke cruise HE511 with links to multibeam raw data files - Justus van Beusekom; Knut Krämer; Christian Winter (PANGAEA, 2020)
Multibeam data were collected during R/V Heincke cruise HE511 acquired by echo sounder system Kongsberg Simrad EM710. Data recording was executed in six separate locations in North Sea within German EEZ. Data are unprocessed and may contain outliers and blunders. Therefore the data should not directly be used for grid calculations and charting projects but need to be edited furthermore. One file contains a measurement period not exceeding ten minutes. The dataset consists of 358 files in Simrad Multibeam Processing Format (*.all) which are compressed with GZIP to size of 19.3 GB (29.2 GB uncompressed). Simrad data files can be processed using the software packages CARIS HIPS/SIPS or with the open source software package MB-System (https://www.mbari.org/products/research-software/mb-system/).